THE INFLUENCE OF SPORTS TRAINING ON THE STABILITY OF THE VESTIBULAR HUMAN APPARATUS - Андреюк, Н.Л. (World of Medicine and Biology, 2017)
The article summarizes the scientific achievements of scientists on the status of the vestibular apparatus of a human and the impact of training on his stability. The role of the vestibular system for representatives of various professional groups and its influence on the ability of a person to work is shown. The results of research on the influence of different types of sport on formation of the vestibular function in athletes and the influence of the functional state of the vestibular system on the manifestation of their motor capabilities are summarized. It is revealed that in the arsenal of fencers there is a huge number of different movements, deviations, blows and injections with a sharp change in combat distance, which act on the vestibular analyzer of an athlete.Representatives of sport games (handball, volleyball, etc.) very depend on the state of the vestibular analyzer, because they have to move quickly, stop sharply, turn and jump. It was revealed that the specialized training and the use of rotational loads in the training process lead to an increase in rates of balance growth, to a rise of the functional stability of the vestibular system and the precise actions associated with it when performing throws, injections, etc.. It is established that the success of the formation of complex motor skills depends on the functional state of the vestibular analyzer. The reaction of an organism to the action of various accelerations, strength abilities, motor efficiency, motor endurance, coordination abilities in athletes is in direct dependence on the functional state of the vestibular analyzer.The vestibular analyzer is a complicated system with large biologically determined bonds with all vital brain structures, which helps maintain a stable balance of a body during rest, movement and orientation of a person in space. The connection between the functional state of the vestibular analyzer and a specialization of an athlete is determined. Athletes engaged in complex sports have a lower threshold of the vestibular sensitivity and the highest degree of the vestibular stability compared with other groups of athletes. This is evidence of positive effect of sports training on the functional stability of the vestibular apparatus. Athletes with the greatest vestibular stability have more clearly expressed performance of specific movements related to this type of sport, their motor functions and manifested coordination ability are better and form faster.The main criterion for assessing the functional status of the vestibular analyzer in athletes is the adequacy of nystagmus reaction of a stimulus and the degree of severity of vegetative and sensory responses. It was established that the development of vestibular functions during a person's life is uneven. Estimation of the vestibular stability does not depend on age, but has a direct dependence on growth of training, sports qualification and a period of a training cycle. Systematic training, starting with childhood, accelerate the process of functional development of the vestibular analyzer.
Keywords: vestibular apparatus; vestibular stability; balance; training